Fintech credit and bank efficiency: International evidence - Tu D. Q. Le; Tin H. Ho; Dat T. Nguyen; Ngo Thanh (International Journal of Financial Studies, 2021)
The expansion of fintech credit around the world is challenging the global banking system. This study investigates the interrelationships between the development of fintech credit and the efficiency of banking systems in 80 countries from 2013 to 2017. The findings indicate a two-way relationship between them. More specifically, a negative relationship between bank efficiency and fintech credit implies that fintech credit is more developed in countries with less efficient banking systems. Meanwhile, a positive impact of fintech credit on the efficiency of banking systems suggests that fintech credit may serve as a wake-up call to the banking system. Therefore, fintech credit should be encouraged by the authorities around the world.
Keywords: E51; G23; O31; 330; banking efficiency; data envelopment analysis; fintech credit; GMM; structural equations model